Football and cultural citizenship in China: a study in three embodiments. Issue 12 (2nd December 2021) - Newman, Joshua I.; Xue, Hanhan; Chen, Ryan; Chen, Yiming; Watanabe, Nicholas M.
Abstract: In this study, we present three 'embodiments' of post-reform footballing China. Starting in 2015, the Chinese Football Association (CFA) initiated a series of reforms to advance player development, increase international success, and broaden the cultural appeal and commercial aspects of the sport. During this time, key footballing bodies have been incorporated into mediatization processes as a way of apprising the public about the state of these initiatives. In this study, we examine how individual players, national teams, and the commercial status of the game – as positioned in political and public discourse – articulate back to narratives and framings of: 1) what it means to represent China; 2) China's ascendency in the global political economy; and 3) how sport as political technology is leveraged in debates about sovereignty and cultural belonging. These three body types reveal a heterogenous, complex, and contested relationality of bodies, cultural representation, and the political mediatized of the footballing State.